Feasibility and Effectiveness of a New Short-Term Psychotherapy Concept for Adolescents With Emotional Dysregulation - Dixius, Andrea; Möhler, Eva (Frontiers in Psychiatry, 2021)
Background: The ‘Stress-Trauma-Symptoms-Regulation-Treatment’ (START) is an innovative manualized short-term treatment program for stabilization and stress resilience in emotionally dysregulated adolescents, based on an approach of stress and management and emotional regulation. The current pilot trial aims to assess the feasibility and effectiveness of the START intervention program for improvement of emotion regulation. Methods: Sixty-six adolescents between the age of 13–18 years admitted to a psychiatric unit for acute emotional or behavioral dysregulation took part in the START program for 5 weeks in an open group setting with two sessions per week (70 min/session). Before treatment, we assessed a history of adverse experience with the Child and Adolescent Trauma Screen (CATS) and the Child Posttraumatic Cognitions Inventory (CPTCI). Before and after treatment, the participants completed the FEEL-KJ, a self-report screening instrument of emotional regulation and coping strategies. Results: A large proportion of this sample had experienced traumatic events based on the CATS (75%) and the CPTCI (82%). The mean FEEL-KJ score significantly decreased after the intervention (d = −0.248, p = 0.037), while no difference was observed with regard to mean level of adaptive emotion regulation strategies (d = 0.202, p = 0.207). A positive effect of the intervention was observed on three components of the adaptive FEEL-KJ scale: accepting (d = 0.289, p = 0.08), forgetting (d = 0.271, p = 0.049) and dealing with anger (d = 0.309, p = 0.034). Conclusion: START demonstrates preliminary evidence for improvement in emotional dysregulation after a 5-weeks course of treatment. Therefore, this short-term intervention can possibly be regarded as a tool to improve emotional stability in children with a high load of trauma-related psychopathology. The results are promising and warrant future studies, specifically randomized controlled trials on the effectiveness of START for strengthening resilience at-risk-populations.